Impact of sand bund removal on seagrass ecosystems: a study of macrobenthic community structure and correlation with macrophytes cover and sediments - Khairun Waheeda, Ahmad Ismail; Teh, Jun Chin; Arshad, Aziz; Wong, Nur Leena W.S. (Elsevier, 2023)
This study investigated the impacts of the removal of sand bund on the macrobenthos community structure, seagrass cover, and sediment particle size in Merambong Shoal, Malaysia. The reclamation project deposited sand bund in the middle of Merambong seagrass shoal, resulting in its division into northern (NS) and southern (SS) halves. Ecosystem changes were monitored over a 31-month period using the transect lines method. Bi-monthly samples were collected for assessment. The results revealed a substantial decline in macrobenthos densities compared to previous studies. However, after the removal of the sand bund, there was a significant increase in macrobenthos density, specifically Polychaeta and Malacostraca, at NS. Seagrass cover at NS was initially lower than SS but showed an increase after the complete removal of the sand blockage. Sediment particle analysis reported a higher silt percentage at NS, indicating greater sedimentation at NS, which was partially sheltered from wave actions.